Peran Sistem Informasi Pemasaran, Kualitas Pelayanan dan Entrepreneurial marketing serta Kepuasan Terhadap Loyalitas Generasi Milenial Berkunjung ke Tempat Wisata - Hidayatullah, syarif; Rachmawati, ike Kusdyah; aristanto, eko; Waris, abdul; Patalo, Ryan Gerry (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2020)
The diversity of tourist attractions in the Jatim Park Group is inseparable from entrepreneurial marketing that is applied by companies with the use of mature market research and in order to support Batu City to become an International Destination City. This study illustrates the influence of marketing information systems, service quality and customer satisfaction on customer loyalty. East Java park group with 6 reservoirs is the location of the study with a total sample of 120 people, with characteristics of millennial age samples (aged between 15-34 years). The results of the research show that the marketing information system does not directly influence loyalty but the marketing information system influences loyalty through the marketing information system, as well as the results of service quality which directly or indirectly affect customer loyalty. The entrepreneurial marketing also has a direct or non-slim influence on customer loyalty through customer satisfaction. This shows the existence of tourist attractions is very necessary the existence of product innovation and differentiation as well as informing customers with an updated marketing information system and still continuing to maintain services if visitors are already in the tourist attractions. Keywords: Marketing Information Systems, Entrepreneurial marketing, Loyalty and Millennial